2014
DOI: 10.1039/c3cc48364a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence turn-on sensor for the detection of palladium ions that operates through in situ generation of palladium nanoparticles

Abstract: A simple and straightforward fluorescence method for the detection of palladium ions at low concentrations has been developed. The mode of operation of the sensor involves in situ generation of palladium nanoparticles (PdNPs), which promote a selective deiodination reaction of iodo-BODIPY that forms highly fluorescent H-BODIPY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Fluorescence sensing protocol is desirable for its easier and cost-effective methodology, good sensitivity and selectivity with high throughput fashion. 16 Most of the reported Pd 2+ sensors are based on fluorescence quenching 17 while a few are "off-on" type. 18 Among the limited fluorescence "on" receptors reported in the literature reaction based chemodosimeter enabling Pd 2+ promoted hydrolytic cleavage of specific bonds as sensing mechanism are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence sensing protocol is desirable for its easier and cost-effective methodology, good sensitivity and selectivity with high throughput fashion. 16 Most of the reported Pd 2+ sensors are based on fluorescence quenching 17 while a few are "off-on" type. 18 Among the limited fluorescence "on" receptors reported in the literature reaction based chemodosimeter enabling Pd 2+ promoted hydrolytic cleavage of specific bonds as sensing mechanism are rare.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment of BODIPY 6 with freshly made HCl gas saturated ethyl acetate could remove the Boc group efficiently in 1 h in almost quantitative yield to afford BODIPY 7 as an amine salt. After neutralization by triethylamine (TEA), amidation reaction between BODIPY 7 and 3-amino-2-naphthoic acid (8) in the presence of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDCI) and 4-dimethylaminopyridine (DMAP) afforded the fluorescent probe BDPÀ Pd in 69% yield. The compound possessed good solubility in common organic solvents and could be purified readily by column chromatography on silica gel.…”
Section: Synthetic Studymentioning
confidence: 99%
“…Kim et al reported a highly sensitive fluorescence sensing system for Pd species based on the reductive deiodination reaction of iodo-BODIPYs, forming highly fluorescent H-BODIPYs promoted by the in situ generation of Pd nanoparticles. [8] Exploiting the photoinduced electron transfer (PET) mechanism, Singh et al synthesized a dithia-dioxa-aza crown ether conjugated BODIPY as a coordination-based fluorescence enhanced probe for Pd 2 + with a detection limit of 1.18 ppb. [9] Recently, another PET-based fluorescence quenching BODIPY probe was prepared by Chang's group [10] which contains a m-bisimidazolylbenzene moiety connected to the meso position of the BODIPY dye by a phenyl acetylene linker, exhibiting a rapid 'ON-OFF' fluorescence response toward Pd 2 + in aqueous buffer media (pH 5.5).…”
Section: Introductionmentioning
confidence: 99%
“…While, the C-I cleavage reaction based probes have relatively strict detection conditions (require additional reagent, eg. NaBH4) for Pd 2+ detection [35,36]. The rhodamine framework is an ideal model for constructing excellent 4 fluorescent probe for Pd 2+ detection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable efforts have been made to develop fluorescent probe for Pd 2+ based on the coordination of Pd 2+ to heteroatom-based ligands [27], Pd 2+ catalyzed depropargylation and deallylation reaction [28][29][30][31][32][33][34], Pd 2+ catalyzed C-I cleavage reaction [35,36], Pd 2+ catalyzed oxidative cyclization reaction [37], and Pd 2+ catalyzed ring-opening reaction [38][39][40][41][42][43] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%